2002
DOI: 10.1038/nsb821
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of a bacterial oxalate transporter

Abstract: The major facilitator superfamily (MFS) represents one of the largest classes of evolutionarily related membrane transporter proteins. Here we present the three-dimensional structure at 6.5 A resolution of a bacterial member of this superfamily, OxlT. The structure, derived from an electron crystallographic analysis of two-dimensional crystals, reveals that the 12 helices in the OxlT molecule are arranged around a central cavity, which is widest at the center of the membrane. The helices divide naturally into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
205
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(215 citation statements)
references
References 20 publications
10
205
0
Order By: Relevance
“…By contrast, Hirae and Subramaniam (12) address a conformation in which OxlT has bound ligand. As a result, this earlier model focuses on aspects of GlpT helix packing that, after an appropriate rigidbody rotation of N-and C-terminal domains (see below), best fit the OxlT 6.5-Å structure (6,7). This finding led to the proposal that helix organization in the GlpT C-terminal domain (GlpT ) is the preferred scheme for both halves of OxlT (OxlT TM1-6 and OxlT TM7-12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Hirae and Subramaniam (12) address a conformation in which OxlT has bound ligand. As a result, this earlier model focuses on aspects of GlpT helix packing that, after an appropriate rigidbody rotation of N-and C-terminal domains (see below), best fit the OxlT 6.5-Å structure (6,7). This finding led to the proposal that helix organization in the GlpT C-terminal domain (GlpT ) is the preferred scheme for both halves of OxlT (OxlT TM1-6 and OxlT TM7-12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Helix organization, symmetry, and connectivity were established first for OxlT, in work based on a low-resolution (6.5 Å) structure obtained by electron crystallography (6,7). Subsequently, higher resolution (3.2-3.5 Å) was achieved by x-ray crystallography of two other MFS members from Escherichia coli, the H ϩ ͞lactose symporter (LacY) and the phosphate͞glycerol 3-phosphate antiporter (GlpT) (8,9).…”
mentioning
confidence: 99%
“…Although speculative, an imaginary folded conformation of MdfA might bring together the two putative substrate recognition clusters to form part of a continuous pathway. According to a recently proposed structural model for 12-helix transporters from major facilitator superfamily (41,42), TM 1, 2, 4, 5, 7, 8, 10, and 11 form a central cavity, which serves as a pathway for substrate transport. It was suggested that different transporters might use different combinations of residues from one or more of these eight helices to achieve the required substrate recognition spectrum (42).…”
Section: Effect Of the Substrates On [ 14 C]nem Labeling Of Single-mentioning
confidence: 99%
“…The advent of crystal structures of several MFS transporters (8)(9)(10)(11) has now placed functional studies of this flavor of transporter on a much firmer footing and allowed for a more rigorous analysis. One of these transporters, the sn-glycerol-3-phosphate (G3P) transporter (GlpT) in the Escherichia coli inner membrane, transports G3P into the cell via an antiport mechanism that is energized by an inorganic phosphate (P i ) gradient (12).…”
mentioning
confidence: 99%